Electroacupuncture alleviates pain-like behaviors through modulating DNMT3a/MOR signaling pathway in CCI rats - Feng Wang; Chengcheng Zhou; Chuangbo Xie; Haoyuan Wang; Xiangyu Li; Gaofeng Zhao (PLoS ONE, 2025)
Neuropathic pain (NP) affects mental health and social functioning of people. Electroacupuncture (EA) has been shown to be effective in relieving NP in clinical practice, but the specific mechanism is still unclear. In our study, we aimed to explore the mechanism of how EA relieving NP by chronic constriction injury (CCI) rat model. EA treatment was performed at acupoints Zusanli (ST36) and Yanglingquan (GB34) after CCI 1 week and after AAV dorsal root ganglion (DRG) injection 3 weeks. EA was performed 30 minutes per day for 7 days. The paw withdrawal threshold (PWT) and paw withdrawal latency (PWL) were checked. The expressions of DNA Methyltransferase 3 Alpha (DNMT3a), Mu opioid receptors (MOR), pain-related signals (Fos, ERK1/2, and pERK1/2) and glial cell activity-related factors (CD11b, Iba1, and GFAP) in spinal cord dorsal horn (SCDH) and DRG were detected by western blotting, quantitative polymerase chain reaction reverse transcription (RT-qPCR). The expressions of DNMT3a and MOR in SCDH and DRG were also observed by immunofluorescence experiments. Our results revealed that CCI increased DNMT3a and decreased MOR expressions in DRG, which could be reversed by EA. EA at Unilateral acupoints Zusanli (ST36) and Yanglingquan (GB34) increased the PWT as well as PWL of the hind paw of CCI rats by down-regulating the expression of pain-related signals (Fos, ERK1/2, and pERK1/2) and glial cell activity-related factors (CD11b, Iba1, and GFAP) in SCDH as well as DRG. EA therapy could produce favorable analgesic results in individuals who experienced pain sensitivity arising from peripheral nerve injury. EA may improve analgesia by increasing MOR expression through the inhibition of DNMT3a in DRG.